The Frequency of Various Phenotypes of Polycystic Ovarian Syndrome in Adolescents, Based on Rotterdam Criteria - Marzieh Akbarzadeh; Tahereh Naderi; Mohammad Hosein Dabbagh Manesh; Hamid Reza Tabatabaee (Shiraz University of Medical Sciences, 2015)
Background: Polycystic Ovarian Syndrome (PCOS) is the most common endocrine disorder among women and is also the cause of infertility due to an- ovulation. Objectives: This study was carried out to determine the prevalence of PCOS phenotypes in Shiraz. Patients and Methods: In this cross-sectional study, 3190 female adolescents aging from 14 to 18 years were randomly selected from Shiraz high schools in 2009. Diagnosis of PCOS was carried out through history, examination according to oligomenorrhea (6 cycles or less in a year), and clinical signs of hyperandrogenism including hirsutism (Ferriman-allwey score of 6 and above), severe acne, and androgenic alopecia. Finally, 146 students entered into this study. The ultrasound was conducted based on Adams criteria .The data analyzed using SPSS-16 software andχ 2and t statistical tests, and P < 0.05 was considered as statistically significant. Results: The prevalence of hirsutism, acne, alopecia, and oligomenorrhea was 3.2% (100 cases), 5% (235 cases), 4.2% (135 cases), and 4.6 % (144 cases), respectively. The incidence rate of menorrhagia was 9.2% (265 cases). Additionally, clinical hyperandrogenism phenotype and oligomenorrhea (HA, OA)were presented in 29 cases (19.9%), clinical Hyperandrogenism phenotype and Polycystic Ovary (HA ,PCO) in 45 cases (30.8%), Oligomenorrhea phenotype and Polycystic Ovary (OA, PCO) in 43 cases (29.5%), and clinical hyperandrogenism phenotype, polycystic ovary, and oligomenorrhea (HA, OA and PCO) in 21 cases (14.5%). Conclusions: Full-blown phenotype (hyper androgenic, Oligomenorrhea and polycystic ovary syndrome), Lowest frequency and phenotype (hyperandrogenic, polycystic ovary syndrome) was the most frequent in this population of Iranian girls. The risk of sex hormone turmoil, psychological effects of skin symptoms (acne and hirsutism), and the high complications of this syndrome in adolescent group necessitate further investigation.